Between the Rock and a Hard Place: The Africa Union and Democracy Promotion in Africa (Journal of Governance and Development (JGD), 2020)
While the Cold War lasted, the Organization of African Unity (OAU) never considered democracy promotion in member states as a priority. What mattered to the body was the safeguard of the sovereignties of member states. The globalization of the third democratic wave however, changed that as democracy promotion, courtesy of Donor’s aid agenda became a core objective of the OAU/AU. Deploying descriptive, historical, and analytical methods of inquiry with a focus on the African Charter on Democracy, Elections, and Governance (ACDEG), this article assesses the extent of AU’s commitments to promoting democracy in Africa. Following an extensive review of conceptual literature on democracy, as well as relevant studies on OAU/AU’s democracy promotion initiatives in Africa, it notes that OAU/AU, no doubt, has robust normative frameworks for dealing with an unconstitutional change of government and other actions that could constitute a threat to the growth of democracy in Africa but in enforcing these frameworks, it is often stuck between a rock and a hard place. It suggests, among others, the strengthening of the enforcement mechanisms of the organization.